Achieving SDGs and addressing health emergencies in Africa: strengthening health promotion - Munodawafa, Davison; Onya, Handsome; Amuyunzu-Nyamongo, Mary; Mweemba, Oliver; Phori, Peter; Kobie, Aminata Grace (SAGE Publications, 2022)
In 1986, the World Health Organization (WHO) convened the first Global Conference on Health Promotion held in Ottawa, Canada. This conference yielded the Ottawa Charter which defined health promotion as the process of enabling people to increase control over, and to improve, their health. A series of conferences followed and in 2005, WHO convened the Sixth Global Conference in Bangkok, Thailand, which yielded the Bangkok Charter for Health Promotion. This Charter for the first time expanded the role of health promotion to include addressing social determinants of health. Ministers of Health from 47 countries of the WHO Regional Office for Africa in 2012 endorsed the Health Promotion: Strategy for the African Region. This Strategy highlighted eight priority interventions required to address health risk factors and their determinants. In 2011, the Rio Political Declaration on Addressing Social Determinants of Health was adopted by Health Ministers and civil society groups to address inequalities and inequities within and between populations. The main action areas were good governance to tackle the root causes of health inequities; promoting participation and ownership; community leadership for action on social determinants; global action on social determinants to align priorities and stakeholders; and monitoring progress on implementation of policies and strategies. Health promotion has been prominent as part of disease outbreak response, including for Ebola and COVID-19. It has been an integral part of improving maternal and child health mortality and morbidity as well as TB, HIV/AIDS and malaria; and lately reducing the impact of noncommunicable diseases, namely diabetes, high blood pressure and cancer. While challenges continue in strengthening health promotion, there have been concerted efforts to place health promotion on the development agenda in countries through Health in All Policies (HiAP), capacity strengthening, monitoring and evaluation, and innovative financing policy options using dedicated tax from tobacco and alcohol, and road use.